Developing Skills of Weaving by Backstrap Loom for OTOP - Chantaroon, Nimnual (Journal for Developing the Social and Community, 2018)
This research aims to study the woven wisdom by the back strap loom, to develop the skills of weaving by the back strap loom, and to services an academic and public relations. The research instrument was the participatory action research (PAR), small group discussion for learning exchange. The sample was the Weaving group of ban Nonsabang, Ban Nasinuan and others. To analyze data by description the phenomenon. The research results were found that; there were changing according to fashion that in the past, it used to be producing by raw materials for their own, however, nowadays they choose the cotton and silk from the factory then suing same weaving process, it was more fabric patterns but lack of identity as high value to attract customers. Bringing wisdom of weaving by the back strap loom with pulling the appropriate features to use in Esarn folk weaving such as striped of Naga, Hook, Jon actions or others. In other hand, there was to design and woven by the back strap loom or development loom for compact enough to carry anywhere, in addition, the development of weaving skills designed to clothe service to those interested in learning easily and could be able to weave in anywhere with comfortable than the one ever use in village.